Development of Coffea arabica L. seedlings obtained from direct somatic embryogenesis - Rezende, Juliana Costa de; Ferreira, Ester Alice; Pasqual, Moacir; Villa, Fabíola; Botelho, César Elias; Carvalho, Samuel Pereira de (Coffee Science - ISSN 1984-3909)
This work aimed to develop embryos and acclimatize seedlings of Coffea arabica L. cv. Rubi produced by direct somatic embryogenesis. For the development of somatic embryos, were evaluated the effect of sucrose (0; 15; 30; 45 and 60 g.L-1) and GA3 (0; 2.5; 5 and 10 mg.L-1). For the development of seedlings, were evaluated the influence of GA3 (0; 2.5; 5; 10 mg.L-¹) and NAA (0; 0.25; 0.5; 1; 2 mg L-¹). The in vitro experiments were carried out in a growth chamber under light intensity of 32 µMol.m-2.s-1, at the temperature of ± 25 1oC and photoperiod of 16 hours. The parameters evaluated were: number of leaves, length of the aerial part and fresh weight of the seedlings. For the seedling acclimatization process two types of substrates were tested (Plantmax® and Plantmax® plus carbonized rice peels (v/v 1:1) and fertilizer with slow-release (Osmocote®) (0, 0.5, 1 and 2 g of the fertilizer per cell). The results indicated that 5.81 mg L-1 GA3 was efficient for the development of coffee somatic embryos and GA3 (10 mg. L-1) in combination with 1mg. L-1 NAA showed efficiency in the development of the seedlings obtained by direct somatic embryogenesis. The best substrate for acclimatization was Plantmax® mixed with carbonized rice peels and 1.68 g per cell of the Osmocote® fertilizer.